Synthesis of N-Acyl-N′-Sulfonyl Hydrazides from Sulfonyl Hydrazides and Activated Amides - An, Yubin; Oh, Jonghoon; Lee, Sunwoo (Synthesis, 2024)
A methodology was developed for synthesizing N-acyl-N'-sulfonyl hydrazides through acyl substitution reactions between activated amides and arylsulfonyl hydrazides. Optimization of the reaction conditions revealed that using Cs₂CO₃ as a base and 1,4-dioxane as a solvent at 25 °C for 12 hours produced the highest yields. Among various amides tested, N-benzoylsuccinimide was found to be the most reactive, with reduced reactivity observed for N-mesityl-, N-tosyl-, and N-Boc-substituted tertiary benzoyl amides. Cross-reactions between a diverse range of N-benzoylsuccinimides and arylsulfonyl hydrazides successfully produced the corresponding N-acyl-N′-sulfonyl hydrazides with yields ranging from 63% to 94%.
Keywords: amides; sulfonyl hydrazides; N-acyl-N′-sulfonyl hydrazides; substitution; room temperature; acylation